Forensic genetic case study: Species identification and traceability of sea turtle caught in illegal trade in Bali, Indonesia - NI PUTU DIAN PERTIWI; MAULID DIO SUHENDRO; NI LUH ASTRIA YUSMALINDA; I NYOMAN GIRI PUTRA; I GUSTI RICCA MAHATMA PUTRI; ENEX YUNI ARTININGSIH; M. DANIE AL-MALIK; NI KADEK DITA CAHYANI; ANDRIANUS SEMBIRING (Society for Indonesian Biodiversity, 2020)
Abstract. Pertiwi NPD, Suhendro MD, Yusmalinda NLA, Putra ING, Putri IGRM, Artinigsih EY, Al Malik MD, Cahyani NKD, Sembiring A. 2020. Forensic genetic case study: Species identification and traceability of sea turtle caught in illegal trade in Bali, Indonesia. Biodiversitas 21: 4276-4283. Although known as protected endangered species, sea turtle trade is still occurring, especially in Indonesia. Understanding the species and population origin of sea turtle being sold in the illegal market is crucial for its conservation, where it will reveal the traceability of sea turtle trade to its population origin in the management unit areas. Thus, genetic forensic has been used as a key investigating tool to help with this problem. In this research, we aim to identify the species and population origin of the sea turtle caught and traded in the illegal market in Bali. Of the 20 samples collected from confiscated sea turtle during illegal trade, by-catch, and a traditional restaurant serving sea turtle meat, 17 samples were successfully analyzed and identified using PCR (polymerase chain reaction) methods. The result identified 15 samples as a green sea turtle (Chelonia mydas), while two samples were olive ridley sea turtle (Lepidochelys olivacea). Mixed Stock Analysis (MSA) with Bayesian indicated that the green sea turtle caught in illegal trade in Bali is originated mostly from the rookeries populations in Berau (29.98%), Terengganu (17.84%), Sarawak (14.84%), and Ashmore Reef (11.85%). Meanwhile, 18 other locations only showed the MSA value below 2%, including the locations of Penang and Perak, Vietnam, Perhentian, Redang, Pahang, Mersing, Sabah Turtle Island Park (TIP), Sipadan, Coral Sea, western New Caledonia, Commonwealth of the Northern Mariana Island and Guam, northern New Guinea, Gulf of Carpenteria, Scott Reef, West Java, North West Self, Cobourg Peninsula, Cocos Keeling Island. Therefore, the exploitation of sea turtle in Bali will impact the decline in the genetic diversity of sea turtles population Indonesia and adjacent locations. Monitoring and protection of sea turtle species in Bali have to be a high priority because Bali is known as the hub for sea turtle illegal trade, and the exploitation of sea turtle in Bali will have an impact on the sea turtle population in other locations.